Getting in touch with the company & interview techniques. RSM CDC case writing training material. / Part 4 : - Yue, Tao, active 2024 (SAGE Business cases., 2024)
Effective communication and preparation are vital when reaching out to a company for case research. This involves sharing your case plan, specifying information needs, and setting clear boundaries. Interview techniques play a crucial role in gathering valuable insights, including principles of active listening and managing the interview process. Common pitfalls to avoid are discussed, such as asking double-barrelled questions and not acknowledging gaps in understanding. Finally, the importance of concluding interviews with clear next steps and follow-ups is emphasized for successful case development.